Knee osteoarthritis pain following medial meniscectomy in the nonhuman primate. Issue 7 (July 2016) - Ogawa, S.; Awaga, Y.; Takashima, M.; Hama, A.; Matsuda, A.; Takamatsu, H.
Summary: Objective: A number of promising compounds developed for osteoarthritic pain have failed to demonstrate clinical efficacy. To enhance preclinical translational research for osteoarthritis, a model of knee osteoarthritis pain was developed in Macaca fascicularis and the effects of two distinct pharmacological classes of drugs were tested on pain-related behavior. Design: Behavioral assessments were developed specifically for the macaque. Baseline knee pressure threshold and weight bearing were assessed prior to a unilateral medial meniscectomy (MMx). Fifteen days following MMx, macaques underwent a once daily exercise regimen for 36 days. Sixty-seven days following MMx, macaques were assigned to one of three treatment groups ( n  = 3/group), either non-steroidal anti-inflammatory drug (NSAID) diclofenac, NK1 receptor antagonist aprepitant or vehicle, and treated for 5 days. Animals were tested 3–4 h after p.o. dosing and testing was performed blinded. Treatment utilized a crossover design—each animal received all treatments—and a 9-day washout period was utilized between treatments. Results: Vehicle-treated macaques consistently demonstrated decreased ipsilateral pressure threshold ("hyperalgesia") and decreased weight bearing. While diclofenac increased weight bearing and pressure threshold, full attenuation of pain was not obtained. No significant improvement of either knee pressure or weight bearing was observed with aprepitant. Conclusions: Unilateral MMx in the macaque evoked pain-related behaviors and knee joint pathology reminiscent of osteoarthritis. The behavioral endpoints were sensitive to NSAID treatment but not sensitive to NK1 receptor block, which parallel clinical findings. The current macaque osteoarthritis model could be used to test potential treatments for osteoarthritis pain.